Simulating Ion Transport with the NP+LEMC Method. Applications to Ion Channels and Nanopores. - Fertig Dávid; Mádai Eszter; Valiskó Mónika; Boda Dezső (Hungarian Journal of Industry and Chemistry, 2017)
We describe a hybrid simulation technique that uses the Nernst-Planck (NP) transport equation to compute steady-state ionic flux in a non-equilibrium system and uses the Local Equilibrium Monte Carlo (LEMC) simulation technique to establish the statistical mechanical relation between the two crucial functions present in the NP equation: the concentration and the electrochemical potential profiles (Boda, D., Gillespie, D., J. Chem. Theor. Comput., 2012 8(3), 824–829). The LEMC method is an adaptation of the Grand Canonical Monte Carlo method to a non-equilibrium situation. We apply the resulting NP+LEMC method to ionic systems, where two reservoirs of electrolytes are separated by a membrane that allows the diffusion of ions through a nanopore. The nanopore can be natural (as the calcium selective Ryanodine Receptor ion channel) or synthetic (as a rectifying bipolar nanopore). We show results for these two systems and demonstrate the effectiveness of the NP+LEMC technique.